Difference in periventricular anastomosis in child and adult moyamoya disease: a vascular morphology study - Ryu, Jiwook; Hamano, Eika; Nishimura, Masaki; Satow, Tetsu; Takahashi, Jun C. (Acta neurochirurgica, 2020)
Backgrounds Periventricular anastomosis (PA), which is a novel term for extended collateral vessels in moyamoya disease (MMD), is reportedly associated with a high risk of intracranial hemorrhage in adult patients. The present study aimed to clarify the similarities and the differences in the development of PA between three MMD groups, classified by age at the time of diagnosis and clinical phenotype. Methods This study included 232 hemispheres of 132 patients with MMD who underwent surgical revascularization. The subjects were classified into child ischemic (CI) group, adult ischemic (AI) group, and adult hemorrhagic (AH) group. We evaluated the lenticulostriate (LSA), thalamic (THA), choroidal (ChA), anterior choroidal (AChA), and posterior choroidal (PChA) anastomosis as well as the posterior cerebral artery (PCA) involvement. The PA scores and the sums of each grade of LSA, THA, and ChA anastomosis were also calculated in all of the cases. Results In a multiple comparison test, the PA scores ( P < 0.01), LSA ( P < 0.01), and ChA anastomosis ( P = 0.013) were more prominent in the CI than in the AI group. The PA scores ( P < 0.01) and LSA ( P = 0.011), ChA ( P < 0.01), AChA ( P < 0.01), and PChA anastomosis ( P = 0.016) were more prominent in the AH group than in the AI group. The CI and AH groups showed similar characteristics except for PCA involvement. After multivariate adjustments using the AI group as a reference group, the PA scores and the positive rates of LSA and ChA anastomosis remained significantly higher in the CI and AH groups. Conclusion The patterns of PA development in the CI and AH groups were similar in that they were more prominent than in the AI group. These findings may contribute to a better understanding of the progression of ischemic and hemorrhagic MMD.